Decision Support System for The Selection of North Sumatra Atlet Drumband By Applying Elimination and Choice Translation Reality (ELECTRE) (Case Study: United States of Drumband Indonesia North Sumatra Region) - S Sunaryo; Natalia Silalahi; M Mesran; Surya Darma Nasution; Guidio Leonarde Ginting (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
Unity Drumband Indonesia (PDBI) Region of North Sumatra is an organizational body engaged in sports groups, which involves players in various musical instruments. In selecting players, PDBI North Sumatra through the committee to conduct strict selection, through a judging system with several stages of a rigorous process. From the selection of participants, compare each criterion one by one to get the best athletes. Implementation of decision support systems is expected to provide the right solution and can assist the jury in generating a decision. Thus the process of selecting athletes can produce a decision directly without a long time. So that accelerate the selection process of drum band athletes who will strengthen the team of North Sumatra. The Elimination and Choice Translation Reality (ELECTRE) method is required in decision support systems for the selection of drum band athletes who will strengthen the North Sumatra team.